KONSEP TERJEMAHAN, TAKWIL, TAFSIR DAN HEURMENITIKA DALAM ILMU AL-QUR'AN - Ismail Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
In order to improve the understanding of the contents of al-Quran, which was revealed in Arabic, the scholars do this in several ways, namely by: (a). Translating, (b). Takwil, (c). Interpret, (d) and (e). Hermeneutic. Fourth this term has a different meaning and purpose. With these four patterns have been born and grown thousands of scientific papers on the Koran, which is used to simplify, speed up and correct understanding the content of the Koran.